Projections of change in key ecosystem indicators for planning and management of marine protected areas: An example study for European seas. (5th February 2018) - Kay, Susan; Butenschön, Momme
Abstract: Marine Protected Areas (MPAs) are widely used as tools to maintain biodiversity, protect habitats and ensure that development is sustainable. If MPAs are to maintain their role into the future it is important for managers to understand how conditions at these sites may change as a result of climate change and other drivers, and this understanding needs to extend beyond temperature to a range of key ecosystem indicators. This case study demonstrates how spatially-aggregated model results for multiple variables can provide useful projections for MPA planners and managers. Conditions in European MPAs have been projected for the 2040s using unmitigated and globally managed scenarios of climate change and river management, and hence high and low emissions of greenhouse gases and riverborne nutrients. The results highlight the vulnerability of potential refuge sites in the north-west Mediterranean and the need for careful monitoring at MPAs to the north and west of the British Isles, which may be affected by changes in Atlantic circulation patterns. The projections also support the need for more MPAs in the eastern Mediterranean and Adriatic Sea, and can inform the selection of sites. Graphical abstract: Highlights: Marine protected areas conserve biodiversity but are affected by climate change. Managers need to understand how multiple indicators, not just temperature, may change in future. A model has been used to project changes in physical and ecosystem indicators for European MPAs. MPAs in the NW Mediterranean and the NW Atlantic are vulnerable. The E Mediterranean needs more MPAs; projections can help with selecting sites.